Importance Performance Analysis para Penjual di Pasar Mama Papua di Wilayah Kabupaten Mimika - Juliana Faluk; I Nyoman Sutapa (Jurnal Titra, 2022)
The measurement regarding the service that government has provide in Mama Papua marketplace to improve the economic which aims on the satisfaction of the vendors about the facilities. This measurement focus on how the people or Papuan mothers could experience great service to create great environmental working place. One of the methods that use for the measurement which is analysis. Analysis is the measurement that use to find the between the performance of a variable and consumer expectations. This shows that it could analyze the difference between the level of interest and the perception of the vendors toward the Mama Papua market service. Moreover, another method that use for the measurement is IPA that stands for importance performance analyze. IPA is the method of measurement that used to determine the level of importance and satisfaction of the vendors in the Mama Papua marketplace by using a quadrant. Optimistically, the facilities should reach the expectation to improve the services at Mama Papua marketplace in Mimika district according to the results.